Victorian Exhibition Culture: The Market Then and the Museum Today - Helmreich, Anne (Romanticism and Victorianism on the Net)

(untitled) (Université de Montréal, 2009)
AbstractThis essay examines the dialectical relationship between the formation of the commercial art market in London over the course of the second half of the nineteenth century and the representation of Victorian art in museum displays of recent decades. With respect to the latter, the essay provides an overview of recent monographic and group exhibitions devoted to Victorian art. It reveals, through the examination of the twinned phenomena of the commercial art market and museological practice, the central role played by exhibition culture in our understanding of Victorian art. It closes by posing questions as to how we might improve our interpretation of Victorian art and culture as presented through museum exhibitions and displays.